RETRACTION NOTICE 1 - Różalski, Antoni; Krajewska, Wanda M.; Mielczarek, Mariusz (Acta Archaeologica Lodziensia, 2023)
This notice refers to: "Article retracted due to plagiarism: Archaeological investigation of the Limes Dacicus in the environs of the Roman fort Bologa, the years 2010-2016". We, the Publisher and Editor-in-Chief of "Acta Archaeologica Lodziensia", have retracted the following article: Rakoczy Jacek. 2016. Archaeological investigation of the Limes Dacicus in the environs of the Roman fort Bologa, the years 2010-2016, "Acta Archaeologica Lodziensia", 62, 69-77 Since publication, it has come to our attention that substantial parts of the paper are plagiarism of Felix Marcu and George Cupcea’s article entitled Recent developments in the Fort of Bologa and on the northwestern Dacian limes published in "Dacia" 2015, volume LIX, pp. 67-82. The author has been informed about the retraction of the article. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as ‘Retracted’.